MANUFACTURING METHOD OF CORROSION PREPARATIONS USING DENTAL PLASTMACC - Щипакин, М. В.; Прусаков, А. В.; Вирунен, С. В.; Скуба, В. В.; Былинская, Д. С. (Scientific Progress & Innovations, 2014)
In article the technique of production of corrosion anatomic preparations with use of stomatologic plastic which is at present used on chair of anatomy of animals of FGBOUVPO "St. Petersburg state academy of veterinary medicine" is stated. As injection hardening liquid we suggest to use two-component plastic "Redont - 03". This plastic is used for production of orthodontic artificial limbs and consists of two components – powder and solvent. As a result of this technique it is possible to make corrosion preparations on cardiovascular system, including the arterial and venous course, and also molds of cavities the tube-bodies. Also, this technique can be used for production of preparations of a bronchial tree and bile-excreting system of a liver. The corrosion preparations received by this technique can be used both in research work, and when carrying out laboratory classes in anatomy of animals.